Metodologia para simulações de arcos elétricos aplicada ao estudo de energia incidente em sistemas elétricos de potência - Londero, Rodolfo Pilar (2022)
Electric arcs are phenomena that occur when the ionization of the air is sufficient to allow the flow of electric current, which can occur due to the separation of energized contacts, such as during the opening of switching devices, or due to a short circuit between two or more conductors separated by a certain distance, which can be caused by poor contact, insulation failure or human error during maintenance of energized equipment. Therefore, the electric arc is one of the most dangerous risks involving activities related to electricity, as it is capable of releasing enormous amounts of energy, almost instantaneously, without any reaction time for anyone nearby. From this, efforts are dedicated to the study of the incident energy (IE) generated by the electric arc, which, in addition to severely damaging the equipment, is responsible for causing burns, putting the lives of workers at risk. However, most studies in the literature are carried out through practical experiments, which have high costs and require long preparation periods. Thus, this dissertation presents a methodology of numerical simulations of electric arcs, using finite element/volume methods, aiming at the study of the EI produced by them. For this, a review is carried out on the main characteristics of electric arcs, the mathematical modeling using the Magnetohydrodynamics Theory and the IE calculation methodology of the IEEE Std 1584/2018 guide, which is widely disseminated and applied for this type of study. From this, the simulation steps are described in detail using the ANSYS Fluent® and ANSYS Electronics Desktop® software, the preparation of the geometries and the EI calculation method based on the simulation data. Finally, different cases are simulated, the results obtained are compared with the results of the IEEE Std 1584/2018 guide which, although they do not present the same final results, allowed to ratify the simulations and corroborate the main characteristics of IE. Therefore, the proposed methodology proved to be satisfactory and opens possibilities for several studies through the variation of several parameters, contributing with agility and cost reduction in the accomplishment of this type of study.